MENUJU SISTEM PENGENDALIAN MANAJEMEN BERTANGGUNG JAWAB SOSIAL STUDI PADA PT. PELINDO MARINE SERVICE SURABAYA - Nurul Kompyurini (Universitas Trunojoyo Madura, 2019)
This study has two objectives. First, to find out how corporate social responsibility (CSR) is defined, and second, to find out whether CSR has been integrated in the management control system (MCS). The theoretical foundation is built from various research articles and literature on corporate social responsibility and management control systems. The object of this research was PT. Pelindo Marine Service Surabaya (PT. PMS). The data in this study comes from interviews with company management.The findings in this study are that the company cannot determine the objectives of social responsibility related to its stakeholders. This contributes to the absence of integration of social responsibility into the MCS. The lack of social responsibility goals related to stakeholder groups has caused the integration of these aspects into MCS to be hampered, and this has the potential to reflect the organization's seriousness in following its stakeholder approach.